KAJIAN TERHADAP PERTIMBANGAN HAKIM TERHADAP HAK-HAK PEREMPUAN BERHADAPAN DENGAN HUKUM BERDASARKAN PERMA NOMOR 3 TAHUN 2017 - IDA MELATI ATASANI (JURIDICA : Jurnal Fakultas Hukum Universitas Gunung Rinjani, 2024)
The purpose of this research is to find out whether the Judge's obligations according to Perma No. 3 of 2007 in terms of adjudicating women's cases in conflict with the law in the case of the Application for Isbat Marriage and Divorce, Complaining Decision No.495/Pdt.G/2023/PA.Sel. and to find out how the Judge considered in Decision No. 495/Pdt.G/2023/PA.Sel Against Women's Rights in conflict with the law. The approach methods used are conceptual, statutory and case approaches. Types of normative juridical research. Based on the research results, the obligations of judges according to Perma No. 3 of 2017, when judging women who are in conflict with the law, judges must be based on the principles of dignity, non-discrimination, gender equality, justice, benefit and legal certainty